THE EXPERIMENTAL HYPOTHYROIDISM MODEL AND HEMATOLOGICAL RESULTS - Tuychiboyev J.; Yusupova U. (Modern American Journals, 2025)
In this study, the changes in hematological parameters of rats under an experimental hypothyroidism model were investigated. The research aimed to identify the disorders caused by thyroid hormone deficiency and to assess alterations in blood composition and immune system activity. Hypothyroidism was induced by oral administration of methimazole to rats for 30 days. The results showed that in the hypothyroid group (M±m, n=6), the number of red blood cells (RBC), hemoglobin (HGB), and hematocrit (HCT) levels significantly decreased compared to the control group. These findings indicate that thyroid hormone deficiency slows down hematopoiesis and reduces oxygen transport capacity. Additionally, an increase in the proportion of granulocytes suggested the activation of inflammatory processes, while elevated lymphocyte counts reflected an adaptive immune response. The enlargement of mean corpuscular volume (MCV) indicated the development of macrocytosis associated with impaired erythropoiesis. This study provides a reliable experimental basis for investigating hematological changes observed in hypothyroid conditions, allowing for the analysis of adaptive mechanisms in the blood system under endocrine dysfunction. The obtained results confirm that hypothyroidism leads to hematological imbalance and demonstrate a complex functional relationship between the blood and immune systems.
Keywords: Hypothyroidism, hematology, thyroid hormones, experimental model.